Steel plate and its manufacturing method
A steel plate composition with controlled elements and microstructures, combined with a TMCP process, addresses ammonia SCC and low-temperature toughness in high-strength steel plates, reducing costs and improving performance for liquefied gas storage tanks.
Patent Information
- Application Number
- JP2023528191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-24
- Filing Date
- 2023-01-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-01-16
AI Technical Summary
Existing methods for manufacturing high-strength steel plates for liquefied gas storage tanks require multiple heat treatments, leading to high equipment and energy costs, while also failing to adequately address ammonia stress corrosion cracking (SCC) and low-temperature toughness.
A steel plate composition with controlled amounts of elements like C, Si, Mn, N, and specific microstructures, combined with a TMCP process, eliminates costly heat treatments and enhances ammonia SCC resistance and low-temperature toughness by optimizing ferrite and bainite volumes and surface hardness.
The solution provides high-strength steel plates with excellent ammonia SCC resistance and low-temperature toughness, suitable for structural components in liquid ammonia environments, without the need for costly heat treatments.
Smart Images

Figure 0007622839000001 
Figure 0007622839000002 
Figure 0007622839000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength steel plate excellent in toughness and corrosion resistance, in particular to a high-strength steel plate excellent in low-temperature toughness and resistance to liquid ammonia stress corrosion cracking suitable for structural members such as tanks used at low temperatures in a liquid ammonia environment, and to a method for producing the same. [Background technology]
[0002] In recent years, the demand for energy has increased, and the transportation of liquefied gas by energy carriers has become more common. In order to operate energy carriers efficiently, the tanks of some carriers may carry not only LPG but also liquid ammonia.
[0003] It is known that liquid ammonia can cause stress corrosion cracking (hereinafter referred to as ammonia SCC) in carbon steel piping, storage tanks, tank cars, line pipes, and other materials that handle liquefied ammonia. For this reason, steel materials with low ammonia SCC susceptibility have been used for steel materials used in liquid ammonia environments, and engineering measures have been taken to suppress ammonia SCC.
[0004] For example, it is known that the occurrence of ammonia SCC is correlated with the strength of the material, and when using carbon steel, efforts are made to avoid stress corrosion cracking caused by ammonia by controlling the yield strength (YS) to 440 MPa or less. On the other hand, in recent years, there has been an increasing demand for higher strength steel plates in view of the increasing size of tanks and the need to reduce the amount of steel used.
[0005] In addition, since liquefied gases such as LPG and liquid ammonia are transported at low temperatures, the steel plates used in storage tanks for these liquefied gases are required to have excellent low-temperature toughness.
[0006] The techniques for satisfying the low-temperature toughness and strength range required for liquefied gas storage tanks as described above are disclosed in Patent Documents 1 and 2. In the techniques described in these documents, high low-temperature toughness and predetermined strength properties are realized by a method in which a thick steel plate that has been cooled after hot rolling is heat-treated several times, or a thick steel plate that has been water-cooled after hot rolling is heat-treated several times. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-140235 [Patent Document 2] Japanese Patent Application Publication No. 10-168516 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the methods described in Patent Documents 1 and 2 above require multiple heat treatments, which poses an economic problem in that the costs for equipment and energy required for the treatment are high.
[0009] The present invention aims to solve the above problems and to provide a high-strength steel plate excellent in ammonia SCC resistance and low-temperature toughness for use in storage tanks, etc. used to store liquefied gas on energy transport ships, and a manufacturing method thereof. [Means for solving the problem]
[0010] In order to achieve the above object, the present inventors have conducted extensive research into various factors affecting the low-temperature toughness and strength properties of steel plates using the TMCP process. As a result, they have found that adding elements such as C, Si, Mn, N, etc. to a steel plate in predetermined amounts or more and controlling the metal structure (microstructure) of the steel plate so that the total volume fraction of the ferrite structure and the bainite structure at the 1 / 2 position of the plate thickness of the steel plate is 60% or more can effectively contribute to achieving the desired low-temperature toughness and strength properties.
[0011] Furthermore, they discovered that by adding elements such as Cu, Cr, Sb, Sn, etc. in specified amounts or more and controlling the hardness at a depth of 1.0 mm from the surface of the steel plate to Hv300 or less, SCC resistance can be obtained in a liquid ammonia environment, and costly heat treatment as in conventional technology can be omitted.
[0012] The present invention has been made based on the above findings, and the gist of the present invention is as follows. 1. In mass percent, C: 0.010~0.200%, Si: 0.01 to 0.50%, Mn: 0.50-2.50%, Al: 0.060% or less, N: 0.0010~0.0100%, P: 0.020% or less, S: 0.0100% or less and O: 0.0100% or less and further comprising Cu: 0.01-0.50%, Cr: 0.01 to 1.00%, Sb: 0.01 to 0.50% and Sn: 0.01 to 0.50% A steel sheet having a composition containing one or more of the above, a CR value calculated by the following formula (1) of 0.70 or more, and the balance being Fe and unavoidable impurities, A hardness characteristic in which the hardness at a position 1.0 mm deep from the surface of the steel plate is Hv300 or less; The steel plate has a metal structure in which, at a half position in the plate thickness of the steel plate, the volume fraction of the bainite structure is 20% or more and the total volume fraction of the ferrite structure and the bainite structure is 60% or more. CR=2.3[Cu]+2.8[Cr]+7.3[Sb]+3.6[Sn]...Formula (1) Here, [X] indicates the content (mass%) of the X element in the steel.
[0013] 2. The composition further comprises, in mass%, Ni: 0.01 to 2.00%, Mo: 0.01 to 0.50% and W: 0.01 to 1.00% The steel plate according to 1 above, containing one or more selected from the following:
[0014] 3. The composition further comprises, in mass%, V: 0.01 to 1.00%, Ti: 0.005 to 0.100%, Co: 0.01 to 1.00%, Nb: 0.005 to 0.100%, B: 0.0001~0.0100%, Ca: 0.0005~0.0200%, Mg: 0.0005 to 0.0200% and REM: 0.0005~0.0200% 3. The steel sheet according to claim 1 or 2, comprising one or more selected from the following:
[0015] In mass%, C: 0.010~0.200%, Si: 0.01 to 0.50%, Mn: 0.50-2.50%, Al: 0.060% or less, N: 0.0010~0.0100%, P: 0.020% or less, S: 0.0100% or less and O: 0.0100% or less and further comprising Cu: 0.01 to 0.50%, Cr: 0.01 to 1.00%, Sb: 0.01 to 0.50% and Sn: 0.01 to 0.50% The steel material contains one or more of the above, has a CR value of 0.70 or more calculated by the following formula (1), and the balance is Fe and unavoidable impurities. The rolling end temperature is set to Ar 3 Hot rolling is performed at or above the transformation point, and then Ar 3A method for producing a steel sheet, comprising cooling from a cooling start temperature equal to or higher than a transformation point to a cooling stop temperature of 600°C or lower, The cooling rate at a position 1.0 mm deep from the surface of the steel plate is 150°C / s or less, and the cooling rate at a position 1 / 2 of the plate thickness of the steel plate is 10°C / s or more. CR=2.3[Cu]+2.8[Cr]+7.3[Sb]+3.6[Sn]...Formula (1) Here, [X] indicates the content (mass%) of the X element in the steel.
[0016] 5. The composition of the steel material is further, in mass%, Ni: 0.01 to 2.00%, Mo: 0.01 to 0.50% and W: 0.01 to 1.00% 5. The method for producing a steel sheet according to 4 above, comprising one or more selected from the following:
[0017] 6. The composition of the steel material is further, in mass%, V: 0.01 to 1.00%, Ti: 0.005 to 0.100%, Co: 0.01 to 1.00%, Nb: 0.005 to 0.100%, B: 0.0001~0.0100%, Ca: 0.0005~0.0200%, Mg: 0.0005 to 0.0200% and REM: 0.0005~0.0200% 6. The method for producing a steel sheet according to 4 or 5 above, comprising one or more selected from the following: Effect of the Invention
[0018] According to the present invention, it is possible to provide, by an inexpensive process, a steel plate which has excellent low-temperature toughness, i.e., impact resistance at low temperatures, and ammonia SCC resistance, and has high strength suitable for structural members such as tanks used at low temperatures and in a liquid ammonia environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described. Note that "%" representing the content of the following components (elements) means "% by mass" unless otherwise specified.
[0020] (1) Composition The composition (chemical composition) of the steel sheet will be described below.
[0021] C: 0.010~0.200% C is the most effective element for increasing the strength of the steel plate produced by the cooling according to the present invention. To obtain this effect, the C content is specified to be 0.010% or more. Furthermore, from the viewpoint of reducing the content of other alloy elements and producing at a lower cost, the C content is preferably 0.013% or more. On the other hand, if the C content exceeds 0.200%, the toughness and weldability of the steel plate are deteriorated. Therefore, the C content is specified to be 0.200% or less. Furthermore, from the viewpoint of toughness and weldability, the C content is preferably 0.170% or less.
[0022] Silicon: 0.01 to 0.50% Si is added for deoxidation. To obtain this effect, the Si content is set to 0.01% or more. It is preferably set to 0.03% or more. On the other hand, if the Si content exceeds 0.50%, it leads to deterioration of the toughness and weldability of the steel plate. Therefore, the Si content is set to 0.50% or less. From the viewpoint of toughness and weldability, it is preferably set to 0.40% or less.
[0023] Mn: 0.50-2.50% Mn is an element that has the effect of increasing the hardenability of steel, and is one of the important elements that must be added to achieve high strength as in the present invention. In order to obtain this effect, the Mn content is specified to be 0.50% or more. Furthermore, from the viewpoint of reducing the content of other alloy elements and manufacturing at a lower cost, the Mn content is preferably 0.70% or more. On the other hand, if the Mn content exceeds 2.50%, the toughness and weldability of the steel plate are reduced, and the alloy cost becomes excessively high. Therefore, the Mn content is specified to be 2.50% or less. Furthermore, from the viewpoint of further suppressing the deterioration of toughness and weldability, the Mn content is preferably 2.30% or less.
[0024] Al: 0.060% or less Al is an element that acts as a deoxidizer and also has the effect of refining crystal grains. In order to obtain such an effect, the Al content is preferably 0.001% or more. On the other hand, if the Al content exceeds 0.060%, oxide-based inclusions increase, cleanliness decreases, and there is concern about deterioration of toughness. Therefore, the Al content is specified to be 0.060% or less. Furthermore, from the viewpoint of further preventing deterioration of toughness, the Al content is preferably 0.050% or less.
[0025] N: 0.0010~0.0100% N contributes to refining the structure and improves the toughness of the steel plate. In order to obtain this effect, the N content is set to 0.0010% or more, and preferably 0.0020% or more. On the other hand, if the N content exceeds 0.0100%, it leads to a decrease in toughness. Therefore, the N content is set to 0.0100% or less. Furthermore, from the viewpoint of further suppressing the decrease in toughness and weldability, the N content is preferably set to 0.0080% or less. Note that, when Ti is present, N can combine with the Ti and precipitate as TiN.
[0026] P:0.020% or less P has adverse effects such as reducing toughness and weldability by segregating at grain boundaries. Therefore, it is desirable to keep the P content as low as possible, but 0.020% or less is acceptable. On the other hand, the lower limit of the P content is not particularly limited and may be 0%, but excessive reduction leads to high refining costs, so from the viewpoint of cost, it is preferable to set the P content to 0.0005% or more.
[0027] S: 0.0100% or less S is an element that exists in steel as sulfide-based inclusions such as MnS, and has adverse effects such as becoming the starting point of fracture and reducing the toughness of the steel plate. Therefore, it is desirable to make the S content as low as possible, but it is acceptable if it is 0.0100% or less. On the other hand, the lower limit of the S content is not particularly limited and may be 0%, but excessive reduction leads to an increase in refining costs, so from the viewpoint of cost, it is preferable to make the S content 0.0005% or more.
[0028] O: 0.0100% or less O is an element that has adverse effects such as forming oxides, becoming the starting point of fracture, and reducing the toughness of the steel plate, and is therefore limited to 0.0100% or less. The O content is preferably 0.0050% or less, and more preferably 0.0030% or less. On the other hand, the lower limit of the O content is not particularly limited and may be 0%, but excessive reduction leads to an increase in refining costs, so from the viewpoint of cost, the O content is preferably 0.0010% or more.
[0029] One or more of Cu: 0.01-0.50%, Cr: 0.01-1.00%, Sb: 0.01-0.50%, and Sn: 0.01-0.50%, and the CR value calculated by formula (1) is 0.70 or more. Cu, Cr, Sb and Sn are particularly important elements in the present invention for improving ammonia SCC resistance. Therefore, in the present invention, it is necessary that one or more of these elements are contained in the above amounts and that the CR value calculated by the following formula (1) is 0.70 or more. CR=2.3[Cu]+2.8[Cr]+7.3[Sb]+3.6[Sn]...Formula (1) Here, [X] indicates the content (mass%) of the X element in the steel. That is, Cu, Cr, Sb, and Sn rapidly form protective corrosion products in a liquid ammonia environment, suppressing stress corrosion cracking. In order to obtain such an effect, when Cu is added, the Cu content must be limited to 0.01% or more, when Cr is added, the Cr content must be limited to 0.01% or more, when Sb is added, the Sb content must be limited to 0.01% or more, and when Sn is added, the Sn content must be limited to 0.01% or more. The formula for calculating the CR value was devised to estimate ammonia SCC resistance from the content of each element, and the higher the CR value, the better the ammonia SCC resistance. By making the CR value 0.70 or more, it becomes possible to suppress stress corrosion cracking in a liquid ammonia environment. On the other hand, excessive addition of Cu, Cr, Sb and Sn deteriorates weldability and toughness, and is also disadvantageous from the viewpoint of alloy cost. Therefore, the Cu content is limited to 0.50% or less, the Cr content to 1.00% or less, the Sb content to 0.50% or less, and the Sn content to 0.50% or less. Preferably, the Cu content is 0.40% or less, the Cr content is 0.80% or less, the Sb content is 0.40% or less, and the Sn content is 0.40% or less. The upper limit of the CR value is not particularly limited, but when the CR value exceeds 7.00, the effect is saturated and the excessive addition of the above elements leads to a rise in price, so that it is preferably about 7.00.
[0030] In the composition of the steel sheet of the present invention, the balance other than the above-mentioned components is Fe and unavoidable impurities, however, the above-mentioned composition may contain the elements described below as necessary.
[0031] One or more selected from Ni: 0.01-2.00%, Mo: 0.01-0.50%, and W: 0.01-1.00% Ni, Mo and W are elements that further improve ammonia SCC resistance, and one or more of these can be contained. In order to obtain such an effect, when Ni is contained, it is preferable to adjust the Ni content to 0.01% or more, when Mo is contained, it is preferable to adjust the Mo content to 0.01% or more, and when W is contained, it is preferable to adjust the W content to 0.01% or more. On the other hand, excessive Ni content leads to deterioration of weldability and increase in alloy cost. In addition, excessive addition of Mo and W deteriorates weldability and toughness, which is also disadvantageous from the viewpoint of alloy cost. Therefore, it is preferable to adjust the Ni content to 2.00% or less, the Mo content to 0.50% or less, and the W content to 1.00% or less. More preferably, the Ni content is adjusted to 1.50% or less, the Mo content to 0.40% or less, and the W content to 0.80% or less, respectively.
[0032] V: 0.01 to 1.00% V is an element that has the effect of improving the strength of a steel sheet, and can be added as desired. In order to obtain such an effect, when V is added, the V content is preferably 0.01% or more. On the other hand, if the V content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy costs. Therefore, when V is added, the V content is preferably 1.00% or less. More preferably, the lower limit of the V content is 0.05% and the upper limit is 0.50%.
[0033] Ti: 0.005 to 0.100% Ti is an element that has a strong tendency to form nitrides and has the effect of fixing N and reducing the amount of solute N, and can be added as desired. Ti can also improve the toughness of the base material and welded parts. In order to obtain these effects, when Ti is added, the Ti content is preferably 0.005% or more. Furthermore, it is more preferable to make it 0.007% or more. On the other hand, if the Ti content exceeds 0.100%, the toughness is rather reduced. Therefore, when Ti is added, the Ti content is preferably 0.100% or less. Furthermore, it is more preferable to make the Ti content 0.090% or less.
[0034] Co: 0.01 to 1.00% Co is an element that has the effect of improving the strength of the steel sheet, and can be added as desired. In order to obtain such an effect, when Co is added, the Co content is preferably 0.01% or more. On the other hand, if the Co content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy costs. Therefore, when Co is added, the Co content is preferably 1.00% or less. More preferably, the lower limit of the Co content is 0.05% and the upper limit is 0.50%.
[0035] Nb: 0.005 to 0.100% Nb is an element that has the effect of reducing the prior austenite grain size and improving toughness by precipitating as carbonitride. In order to obtain such an effect, when Nb is added, the Nb content is set to 0.005% or more. More preferably, it is set to 0.007% or more. On the other hand, when the Nb content exceeds 0.100%, a large amount of NbC precipitates, and the toughness decreases. Therefore, when Nb is added, the Nb content is preferably set to 0.100% or less. More preferably, it is set to 0.060% or less.
[0036] B: 0.0001 to 0.0100% B is an element that has the effect of significantly improving hardenability even when added in a small amount. In other words, it can improve the strength of the steel sheet. In order to obtain this effect, when B is added, the B content is preferably 0.0001% or more. On the other hand, when the B content exceeds 0.0100%, the weldability decreases. Therefore, when B is added, the B content is preferably 0.0100% or less. More preferably, the lower limit of the B content is 0.0010% and the upper limit is 0.0030%.
[0037] Ca: 0.0005~0.0200% Ca is an element that combines with S and has the effect of suppressing the formation of MnS and the like that elongates in the rolling direction. That is, by adding Ca, the morphology of sulfide-based inclusions can be controlled to be spherical, and the toughness of welds and the like can be improved. In order to obtain such an effect, when Ca is added, the Ca content is preferably 0.0005% or more. On the other hand, if the Ca content exceeds 0.0200%, the cleanliness of the steel decreases. The decrease in cleanliness leads to a decrease in toughness. Therefore, when Ca is added, the Ca content is preferably 0.0200% or less. More preferably, the lower limit of the Ca content is 0.0020% and the upper limit is 0.0100%.
[0038] Mg: 0.0005~0.0200% Mg, like Ca, is an element that combines with S and inhibits the formation of MnS and the like that elongates in the rolling direction. That is, by adding Mg, the shape of sulfide-based inclusions can be controlled to be spherical, and the toughness of welds and the like can be improved. In order to obtain such an effect, when Mg is added, the Mg content is preferably 0.0005% or more. On the other hand, when the Mg content exceeds 0.0200%, the cleanliness of the steel decreases. The decrease in cleanliness leads to a decrease in toughness. Therefore, when Mg is added, the Mg content is preferably 0.0200% or less. More preferably, the lower limit of the Mg content is 0.0020% and the upper limit is 0.0100%.
[0039] REM: 0.0005~0.0200% Like Ca and Mg, REM (rare earth metal) is an element that combines with S and inhibits the formation of MnS, etc., which elongates in the rolling direction. That is, by adding REM, the shape of sulfide-based inclusions can be controlled to be spherical, and the toughness of welds, etc. can be improved. When REM is added to obtain such an effect, the REM content is preferably 0.0005% or more. On the other hand, if the REM content exceeds 0.0200%, the cleanliness of the steel decreases. The decrease in cleanliness leads to a decrease in toughness. Therefore, when REM is added, the REM content is preferably 0.0200% or less. More preferably, the lower limit of the REM content is 0.0020% and the upper limit is 0.0100%.
[0040] (2) Hardness characteristics and metal structure In addition to having the above-mentioned composition, the steel sheet of the present invention has a hardness characteristic of Hv300 or less at a position 1.0 mm deep from the surface of the steel sheet (also referred to as the 1.0 mm position in the present invention). Furthermore, the steel plate of the present invention has a metal structure in which, at the 1 / 2 position of the plate thickness of the steel plate (which in the present invention means the position at a depth of 1 / 2 of the plate thickness; hereinafter, this is also simply referred to as the 1 / 2 position or the plate thickness center), the volume fraction of the bainite structure (hereinafter, this is also simply referred to as bainite) is 20% or more, and the total volume fraction of the ferrite structure (hereinafter, this is also simply referred to as ferrite) and the bainite is 60% or more. The reasons for limiting the hardness characteristics and metal structure of the steel sheet as described above will be explained below.
[0041] [Hardness at 1.0mm position is Hv300 or less] The hardness at the 1.0 mm position is Hv300 or less. If a high hardness region exists at the very surface layer of the steel sheet, specifically at the 1.0 mm position from the surface of the steel sheet, stress corrosion cracking in a liquid ammonia environment is promoted. Therefore, in the steel sheet of the present invention, the hardness at the 1.0 mm position is adjusted to Hv300 or less to ensure excellent ammonia SCC resistance. The lower limit of the hardness at the 1.0 mm position is not particularly limited, but is preferably about Hv130. Here, the hardness can be calculated by measuring the Vickers hardness at multiple points (for example, 100 points) at 0.5 mm positions.
[0042] [At the 1 / 2 position, the volume fraction of bainite is 20% or more, and the total volume fraction of ferrite and bainite is 60% or more] The structure at the 1 / 2 position must have a bainite volume fraction of 20% or more and a total volume fraction of ferrite and bainite of 60% or more. If excessive ferrite is formed, it will result in a decrease in strength or toughness. If the total volume fraction of ferrite and bainite is less than 60%, the volume fractions of other structures, i.e., island martensite structure, martensite structure, pearlite structure, and austenite structure, will increase, making it impossible to obtain sufficient strength or toughness and to satisfy mechanical properties. The total volume fraction of ferrite and bainite may be 100%.
[0043] Here, the ferrite means ferrite formed during the cooling process before tempering, and the bainite means bainite formed during the cooling process before tempering. The reason for specifying the microstructure at the center of the plate thickness is that the microstructure at the center of the plate thickness affects the strength characteristics of the center of the plate thickness, and that the strength characteristics at the center of the plate thickness affect the strength of the entire steel plate.
[0044] The remaining structure, which accounts for 40% or less by volume, may include a martensite structure in addition to a pearlite structure and an austenite structure. The fraction of each structure in the remaining structure does not need to be particularly limited, but it is preferable that the remaining structure is a pearlite structure. The volume fractions of various microstructures can be measured by the methods described in the Examples below.
[0045] (3) Manufacturing conditions The manufacturing method of the present invention comprises the steps of: C: 0.010-0.200%, Si: 0.01-0.50%, Mn: 0.50-2.50%, Al: 0.060% or less, N: 0.0010-0.0100%, P: 0.020% or less, S: 0.0100% or less, and O: 0.0100% or less; and further comprises one or more of Cu: 0.01-0.50%, Cr: 0.01-1.00%, Sb: 0.01-0.50%, and Sn: 0.01-0.50%, and the CR value calculated by the above formula (1) is 0.70 or more, and further comprises Ni: 0.01-2.00%, Mo: 0.01-2.00%, and A steel material having a composition containing at least one selected from 0.01-0.50% and W: 0.01-1.00% and / or at least one selected from 0.01-1.00% V, 0.005-0.100% Ti, 0.01-1.00% Co, 0.005-0.100% Nb, 0.0001-0.0100% B, 0.0005-0.0200% Ca, 0.0005-0.0200% Mg, and 0.0005-0.0200% REM, with the balance being Fe and unavoidable impurities, is heated and hot-rolled, and then cooled as specified according to the present invention. The reasons for limiting the manufacturing conditions of the steel plate will be explained below. First, the manufacturing conditions of the steel material do not need to be particularly limited, but it is preferable to melt molten steel having the above-mentioned composition by a known melting method such as a converter, and form the steel material into a slab or the like of a predetermined size by a known casting method such as a continuous casting method. There is no problem in forming the steel material into a slab or the like of a predetermined size by the ingot casting-disassembly rolling method.
[0046] The steel material thus obtained is either directly hot rolled without cooling, or is reheated and then hot rolled. 3 The transformation temperature (hereinafter simply referred to as Ar 3 The transformation point is reached by hot rolling. 3 Cooling is performed under specified conditions from a cooling start temperature above the transformation point to a cooling stop temperature below 600°C.
[0047] The heating temperature of the steel material (the temperature when subjected to hot rolling) is not particularly limited, but if the heating temperature is too low, the deformation resistance increases, which increases the load on the hot rolling machine and may make hot rolling difficult. On the other hand, if the heating temperature is too high and exceeds 1300°C, oxidation becomes significant, which increases the oxidation loss and increases the risk of a decrease in yield. For these reasons, the heating temperature is preferably 950°C or higher and 1300°C or lower.
[0048] (Hot Rolling) [Rolling end temperature: Ar 3 Above the transformation point] In the present invention, after heating to the above temperature, hot rolling is started and Ar 3 The hot rolling is terminated at or above the transformation point. The rolling end temperature is Ar 3 If the temperature is below the transformation point, ferrite is generated and the generated ferrite is affected by processing, which deteriorates the toughness. Furthermore, the load on the hot rolling machine increases. Therefore, the rolling end temperature in hot rolling is set to Ar 3 The rolling end temperature in the hot rolling is preferably Ar 3 The temperature is the transformation point +10° C. or more. On the other hand, if the rolling end temperature exceeds 950° C., the structure may become coarse and the toughness may deteriorate, so the rolling end temperature is preferably 950° C. or less. Here, Ar 3 The transformation point can be calculated using the following formula. Ar 3 (℃) = 910-310 x C-80 x Mn-20 x Cu-15 x Cr-55 x Ni-80 x Mo Here, each element indicates the content (mass%) of the element in the steel.
[0049] (cooling) [Cooling start temperature: Ar 3 Above the transformation point] Next, for the hot-rolled steel sheets, Ar 3 Cooling is performed from a temperature above the transformation point. 3 Below the transformation point, excessive ferrite is generated, resulting in insufficient strength. Therefore, the cooling start temperature is set to Ar 3Above the transformation point.
[0050] [Cooling stop temperature: 600℃ or less] In the present invention, after the completion of hot rolling, cooling is performed under predetermined conditions up to an arbitrarily set cooling stop temperature of 600°C or less, thereby making it possible to obtain a predetermined volume fraction of ferrite and bainite in the center of the plate thickness. Here, if the cooling stop temperature exceeds 600°C, excessive ferrite structure and pearlite structure may be generated, which may lead to insufficient strength. Therefore, the cooling stop temperature is specified to be 600°C or less. Although there is no particular limit to the lower limit of the cooling stop temperature, if the cooling stop temperature is too low, the volume fraction of the island martensite structure becomes too high, and the toughness decreases. Therefore, the cooling stop temperature is preferably 200°C or more. The cooling stop temperature is the temperature at the 1 / 2 position of the steel plate.
[0051] [Cooling rate at 1.0 mm position: 150℃ / s or less] In the above cooling, if the cooling rate at the 1.0 mm position exceeds 150° C. / s, the hardness at the 1.0 mm position exceeds Hv300, and the ammonia SCC resistance deteriorates. Therefore, the cooling rate at the 1.0 mm position is specified to be 150° C. / s or less. On the other hand, the lower limit of the cooling rate is not particularly limited, but if the cooling rate is too low, ferrite structure or pearlite structure may be generated excessively, which may lead to insufficient strength or deterioration of toughness. Therefore, from the viewpoint of more reliably preventing this, it is preferable to set the cooling rate to 50° C. / s or more. The cooling rate can be controlled by intermittent cooling including cooling stop periods. It is difficult to physically measure the temperature at the 1.0 mm position directly. However, the temperature distribution in the plate thickness cross section, particularly the temperature at the 1.0 mm position, can be calculated in real time by performing a differential calculation using, for example, a process computer based on the surface temperature at the start of cooling measured by a radiation thermometer and the surface temperature at the target time of cooling stop.
[0052] [Cooling rate at 1 / 2 position: 10℃ / s or more] Cooling at a 1 / 2 position at a cooling rate of 10°C / s or more is an essential process for obtaining a steel plate with high strength and high toughness, and cooling at a high cooling rate can increase strength through transformation strengthening. To obtain such an effect, the cooling rate at the 1 / 2 position during cooling according to the present invention is specified to be 10°C / s or more. If the cooling rate is less than 10°C / s, ferrite and pearlite are excessively formed, and sufficient strength cannot be obtained. Therefore, the cooling rate at the 1 / 2 position of the plate thickness is specified to be 10°C or more. On the other hand, although there is no particular upper limit to the cooling rate, if the cooling rate is too high, the volume fraction of island martensite becomes too high, which may lead to deterioration of toughness. Therefore, the cooling rate at the 1 / 2 position is preferably 80° C. / s or less. The cooling rate can be controlled by intermittent cooling including cooling stop periods. It is difficult to physically measure the temperature at the 1 / 2 position directly. However, the temperature distribution in the plate thickness cross section, particularly the temperature at the 1 / 2 position, can be calculated in real time by performing a differential calculation using, for example, a process computer based on the surface temperature at the start of cooling measured by a radiation thermometer and the surface temperature at the target time of cooling stop.
[0053] The cooling rate at the 1.0 mm position and the cooling rate at the 1 / 2 position can each be changed by, for example, adjusting the cooling start temperature, the amount of water, and the like in a composite manner.
[0054] By manufacturing a steel material having the above-mentioned composition under the above-mentioned manufacturing conditions, a steel plate having the composition, hardness characteristics, and metal structure according to the present invention can be obtained. The steel plate thus obtained has excellent strength characteristics and toughness. Here, excellent strength characteristics are a yield strength YS (yield point YP when there is a yield point, and 0.2% proof stress σ0.2 when there is no yield point) of 360 MPa or more and a tensile strength (TS) of 490 MPa or more. Furthermore, excellent toughness is a vTrs according to JIS Z 2241 of -30°C or less.
[0055] In the production method according to the present invention, any item not described in this specification can be carried out in a conventional manner. EXAMPLES
[0056] Steels (steel types A to AH, the remainder being Fe and unavoidable impurities) having the chemical compositions shown in Table 1 were formed into slabs by continuous casting, and these were used to produce thick steel plates (Nos. 1 to 44) having a plate thickness of 30 mm. Next, hot rolling and cooling were performed in sequence under the conditions shown in Table 2 to obtain steel plates. For the obtained steel plates, the structure fraction of the metal structure at the 1 / 2 position in the plate thickness, the hardness at the position 1.0 mm from the steel plate surface, the strength characteristics and toughness, and the ammonia SCC resistance were each measured. The test methods are as follows. The results are also shown in Table 2.
[0057] [Metal structure fraction at 1 / 2 position] A sample was taken from each steel plate so that the 1 / 2 position (center of plate thickness) was the observation surface. The sample was then mirror-polished and further etched with nital, after which an image of a 10 mm x 10 mm area was taken at a magnification of 500 to 3000 times using a scanning electron microscope (SEM). The image was then analyzed using an image analyzer to determine the areal fraction of the microstructure (structural fraction of the metal structure). When the anisotropy of the microstructure is small, the areal fraction corresponds to the volume fraction, and therefore in the present invention, the areal fraction was regarded as the volume fraction.
[0058] In this example, the discrimination for determining the fraction of the metal structure of the sample was performed as follows: In the above-mentioned photographed image, polygonal ferrite was discriminated as ferrite (F in Table 2), and the structure having elongated, grown lath-like ferrite and containing carbides with a circle equivalent diameter of 0.05 μm or more was discriminated as bainite (B in Table 2).
[0059] [Hardness at 1.0mm] For the cross section perpendicular to the rolling direction of each steel plate, Vickers hardness (HV10) was measured at 100 points at 1.0 mm positions in accordance with JIS Z 2244, and the maximum value was calculated.
[0060] [Strength characteristics] From the full thickness of each steel plate, JIS Z 2201 No. 1B test pieces were taken perpendicular to the rolling direction and perpendicular to the plate thickness direction, and tensile tests were performed as described in JIS Z 2241 to measure the yield strength YS (yield point YP when there is a yield point, 0.2% proof stress σ0.2 when there is no yield point) and tensile strength (TS). Steel plates with a yield strength of 360 MPa or more and a tensile strength of 490 MPa or more were evaluated as having excellent strength properties.
[0061] [Toughness] A JIS Z 2202 V-notch test piece was taken from a portion 1 mm removed from the surface side of each steel plate in the rolling direction, and a Charpy impact test was performed in accordance with JIS Z 2242 to measure vTrs (fracture transition temperature). Steel plates with a vTrs of -30°C or less were evaluated as having excellent toughness.
[0062] [Ammonia SCC resistance] The ammonia SCC resistance was evaluated by an accelerated test in which a four-point bending test was performed in a test solution and constant-potential anodic electrolysis was performed to accelerate corrosion. Specifically, the following steps were taken: Test pieces measuring 5 mm thick x 15 mm x 115 mm were taken from the surface of the steel plates, ultrasonically degreased in acetone for 5 minutes, and then subjected to 4-point bending to a stress of 100% YS of the actual yield strength of each steel plate. The 4-point bending test pieces were placed in a test cell and filled with a solution of 12.5 g of ammonium carbamate and 1 L of liquid ammonia. The potentiostat was used to control the flow of +2.0 V vs Pt to the test pieces, and the pieces were immersed at room temperature (25°C). If no cracks were observed after 168 hours of immersion, the ammonia SCC resistance was judged to be "good", and if cracks were observed, the ammonia SCC resistance was judged to be "poor".
[0063] [Table 1]
[0064] [Table 2] TIFF0007622839000003.tif223121
[0065] As can be seen from Tables 1 and 2, all of the inventive examples (Nos. 1 to 26) have a yield strength YS of 360 MPa or more, a tensile strength TS of 490 MPa or more, and a vTrs of -30°C or less, so that the steel plates obtained have excellent toughness at low temperatures and also have excellent ammonia SCC resistance.
[0066] On the other hand, although the composition of Nos. 27 to 31 is within the range of the present invention, the manufacturing method is outside the range of the present invention, and therefore the desired metal structure or hardness characteristics are not obtained, resulting in inferior yield strength YS, tensile strength TS, low temperature toughness, or ammonia SCC resistance.
[0067] In addition, Nos. 32 to 44 have steel compositions outside the range of the present invention, and therefore are inferior in either yield strength YS, tensile strength TS, low temperature toughness, or ammonia SCC resistance. In the present invention, the steel composition may be considered as the steel plate composition as it is.
Claims
1. In mass percent, C: 0.010-0.200%, Si: 0.01 to 0.50%, Mn: 0.50 to 2.50%, Al: 0.060% or less, N: 0.0010-0.0100%, P: 0.020% or less, S: 0.0100% or less; O: 0.0100% or less and further comprising Cu: 0.01 to 0.50%, Cr: 0.01-1.00%, Sb: 0.01 to 0.50% and Sn: 0.01-0.50% A steel sheet having a component composition containing one or more of the following, a CR value calculated by the following formula (1) being 0.70 or more, and the balance being Fe and unavoidable impurities, A hardness characteristic in which the hardness at a position 1.0 mm deep from the surface of the steel plate is Hv300 or less; and a metal structure in which, at a half position in the sheet thickness of the steel plate, a volume fraction of a bainite structure is 20% or more and a total volume fraction of a ferrite structure and a bainite structure is 60% or more. CR=2.3[Cu]+2.8[Cr]+7.3[Sb]+3.6[Sn]...Formula (1) Here, [X] indicates the content (mass%) of the X element in the steel.
2. The composition further comprises, in mass%, Ni: 0.01-2.00%, Mo: 0.01 to 0.50% and W: 0.01~1.00% The steel sheet according to claim 1, comprising one or more selected from the following:
3. The composition further comprises, in mass%, V: 0.01-1.00%, Co: 0.01 to 1.00%, Nb: 0.005-0.100%, B: 0.0001 to 0.0100%, Ca: 0.0005-0.0200%, Mg: 0.0005 to 0.0200% and REM: 0.0005-0.0200% The steel sheet according to claim 1 or 2, comprising one or more selected from the following:
4. In mass percent, C: 0.010-0.200%, Si: 0.01 to 0.50%, Mn: 0.50 to 2.50%, Al: 0.060% or less, N: 0.0010-0.0100%, P: 0.020% or less, S: 0.0100% or less; O: 0.0100% or less and further comprising Cu: 0.01 to 0.50%, Cr: 0.01-1.00%, Sb: 0.01 to 0.50%; and Sn: 0.01~0.50% The steel material has a composition in which the CR value calculated by the following formula (1) is 0.70 or more, and the balance is Fe and unavoidable impurities. 3 The steel is then hot-rolled to a temperature above the transformation point, and then Ar 3 A method for producing a steel sheet, comprising cooling from a cooling start temperature equal to or higher than a transformation point to a cooling stop temperature of 600°C or lower, the cooling is performed at a cooling rate of 150°C / s or less at a position 1.0 mm deep from the surface of the steel plate, and at a cooling rate of 10°C / s or more at a position 1 / 2 of the plate thickness of the steel plate; and the steel plate has a hardness characteristic of Hv300 or less at a position 1.0 mm deep from the surface of the steel plate, and a metal structure in which a volume fraction of bainite structure is 20% or more and a total volume fraction of ferrite structure and bainite structure is 60% or more at the position 1 / 2 of the plate thickness of the steel plate. CR=2.3[Cu]+2.8[Cr]+7.3[Sb]+3.6[Sn]...Formula (1) Here, [X] indicates the content (mass%) of the X element in the steel.
5. The composition of the steel material further comprises, in mass%, Ni: 0.01-2.00%, Mo: 0.01 to 0.50% and W: 0.01~1.00% The method for producing a steel sheet according to claim 4, further comprising the step of:
6. The composition of the steel material further comprises, in mass%, V: 0.01-1.00%, Co: 0.01 to 1.00%, Nb: 0.005-0.100%, B: 0.0001 to 0.0100%, Ca: 0.0005-0.0200%, Mg: 0.0005 to 0.0200% and REM: 0.0005-0.0200% The method for producing a steel sheet according to claim 4 or claim 5, further comprising:
Citation Information
Patent Citations
Method of laying sheet at bottom of water
JP1980030062A
Production of low yield ratio and high tension strength steel excellent in weldability and low temperature toughness
JP1998140235A
Production of low yield ratio high tensile strength steel excellent in weldability and low temperature toughness
JP1998168516A
Method for manufacturing low yield ratio high tensile strength steel plate excellent in low temperature toughness
JP2011105963A
Low-yield-ratio thick steel plate
JP2019214751A